2010
DOI: 10.4103/0019-5545.74306
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long-term outcome of first-episode schizophrenia: A ten-year follow-up study

Abstract: Objective:Schizophrenia is a severe mental disorder for which final outcomes continue to be unfavorable. The main objectives of this research were to examine and determine the baseline predictors of outcome status of first-episode schizophrenia in a long-term follow-up of ten years and of recovery ten years later.Materials and Methods:The study was carried out in a non-governmental, psychiatric hospital and participants consisted of patients available for assessment ten years following their initial diagnosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…An Indian prospective study with a 10‐year follow‐up focused on predictors of long‐term outcome . The Clinical Global Impression Scale‐Improvement (CGIS‐I) was used to assess overall clinical change.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An Indian prospective study with a 10‐year follow‐up focused on predictors of long‐term outcome . The Clinical Global Impression Scale‐Improvement (CGIS‐I) was used to assess overall clinical change.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the reason why insidious onset is associated with worse prognosis is that it leads to a longer DUP. The finding that higher levels of negative symptoms at baseline predict poorer outcome perhaps implies insidious onset. Other predictors of worse prognosis include earlier age of onset, higher levels of aggression and worse cognitive functioning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal 10 year study in first episode schizophrenia patients demonstrated that treatments received, social support, compliance and delay in treatment all affect outcome in schizophrenia. 30 A review on Indian research in schizophrenia has also emphasized that elucidating factors affecting recovery and non recovery in schizophrenia shall help in the primary prevention of the problem itself. 31 Women in India has been shown to often have better outcomes in schizophrenia than men while delay in seeking treatment is often longer in the case of women.…”
Section: Discussionmentioning
confidence: 99%
“…General information of the patient was collected in a proforma and information on psychiatric illness was collected in psychiatric questionnaire developed by Michael C. Hilton. 19 Drug abuse screening test (DAST) developed by Harvey A. Skinner, alcohol use disorders identification test (AUDIT) developed by WHO, Suicide risk scale developed by National Health and Medical Research Council, Positive and negative syndrome scale (PANSS) developed by SR Kay et al [20][21][22][23][24] were used to assess the patients. Data entry and analysis were done using SPSS software version 17.0.…”
Section: Methodsmentioning
confidence: 99%